Pengaruh pH Asam Terhadap Kekuatan Mekanik Fiber E-Glass: Systematic Review - Lukman Sikha Prasetyo; Etny Dyah Harniati; Budiono Budiono (Universitas Muhammadiyah Semarang, 2022)
Background: Dental fibers were first introduced by Smith (1960) which are used in various fields of dentistry. Dental fibers are classified into two categories, natural and synthetic. Glass fiber that is often used in dentistry is E-glass fiber because of its resistance to chemical reactions, has good aesthetic properties, has almost the same mechanical properties as dentin and is biocompatible. In the oral cavity, acidic conditions occur due to consumption of food and beverages containing acid. Acidic conditions in the oral cavity can affect the mechanical properties of the composite resin. Factors that affect the mechanical properties of fiber reinforced composite are the properties of the composite material and fiber used, fiber quantity, fiber position, fiber direction, fiber adhesion to the composite matrix. To determine and study the effect of acidic pH on the mechanical strength of e-glass fibers. Method: This type of research is a literature review using a systematic review approach.Result: The decrease in compressive strength and resistance was influenced by structural disturbances and loss of most components due to acid exposure. The decrease in the tensile strength of the glass fiber increases the time associated with immersion of the fiber surface which can interfere with the continuity of the e-glass network. Acidic drinks, carbonated drinks, and alcohol can produce erosion on the surface of the composite resin. The longer the immersion, the more solution particles that enter the resin microporosity space and reduce the strength of the composite resin.Conclusion: The mechanical strength of e-glass fiber will decrease with the length of exposure to acid. Types of acids that can affect the decline in mechanical strength are strong acids such as hydrochloric acid (HCl), sulfuric acid (H2SO4), nitric acid (HNO3), and phosphoric acid (H3PO4).